Dimensions of transformational leadership and its role in achieving the strategic plans - Taha Mahdjoub Taha, Nahla; Adbulh Mohamed Chikh Idris, Eshraga (Finance and Business Economies Review, 2019)
The study aimed to know the role of the dimensions of transformational leadership (ideal influence, inspirational motivation, intellectual stimulation, individual considerations) in achieving the strategic plan at the National University of Rabat, Sudan, because of the importance of transformational leadership dimensions. The descriptive analytical method was used, and the questionnaire was used as a tool to collect the data needed to test the hypotheses of the study based on the lack of a role for transformative leadership dimensions in achieving the strategic plan at the National University of Rabat. One of the most important results of the study is the strong and direct correlation between the dimensions of transformational leadership and the realization of the strategic plan at the National University of Rabat. Therefore, the study recommends increasing attention to the application of transformative leadership dimensions in order to achieve the strategic plan of the university as required